Torsional load-bearing capacity of half-shell segments for prestressed concrete towers. (15th September 2021) - Klein, Fabian; Marx, Steffen
Highlights: An engineering model for torsional load-bearing behaviour of half-shell structures is presented. The tension member analogy and the load redistribution principle are combined for stress calculation. The analytical approach significantly simplifies the calculation of the additional warping stresses. The study shows the separation of individual load transfer effects in assembled half-shell structures. Abstract: This article deals with the torsional load-bearing behaviour of concrete half-shell structures. The analogy between the bending stressed tension members according to second order theory and torsional members with warping hindered cross-section leads to a significantly simplified calculation of the additionally occurring warping stresses. This eliminates the need for the laborious solution of complex differential equations of the classical torsional warping theory to determine the load-bearing behaviour of warped cross-sections. The load redistribution approach projects the global torsion load of the segment tower onto the individual half-shell. The combination of the two approaches enables the analytical calculation of the torsional load-bearing behaviour of the concrete half-shell construction as a function of the global torsional moment and the system variables of the half-shell. The objective is to investigate and describe the torsional load-bearing behaviour of segmented half-shell structures in an engineering model. Compared to closed circular ring segments, the vertical joints have a significant influence, especially on the torsional rigidity. In order to determine the horizontal joint bearing capacity of these innovative constructions, it is essential to understand the load transfer of the torsional load. The presented approach allows to separate the individual effects of the load transfer in half-shell constructions from each other and thus to identify the factors influencing the torsional load-bearing behaviour.